Climate variability and change or multiple stressors? Farmer perceptions regarding threats to livelihoods in Zimbabwe and Zambia - Mubaya, Chipo Plaxedes; Njuki, Jemimah; Mutsvangwa, Eness Paidamoyo; Mugabe, Francis Temba; Nanja, Durton (Elsevier, 2021)
Climate variability is set to increase, characterised by extreme conditions in Africa. Southern Africa will likely get drier and experience more extreme weather conditions, particularly droughts and floods. However, while climate risks are acknowledged to be a serious threat to smallholder farmers’ livelihoods, these risks do not exist in isolation, but rather, compound a multiplicity of stressors. It was important for this study to understand farmer perceptions regarding the role of climate risks within a complex and multifarious set of risks to farmers’ livelihoods. This study used both qualitative and quantitative methods to investigate farmers’ perceptions regarding threats to livelihoods in southern Zambia and south-western Zimbabwe. While farmers report changes in local climatic conditions consistent with climate variability, there is a problem in assigning contribution of climate variability and other factors to observed negative impacts on the agricultural and socio-economic system. Furthermore, while there is a multiplicity of stressors that confront farmers, climate variability remains the most critical and exacerbate livelihood insecurity for those farmers with higher levels of vulnerability to these stressors.